IMPLEMENTASI METODE PROTOTYPE PADA PEMBUATAN WEBSITE DESTINATION BRANDING PARIWISATA “PANTAITELUKAWUR.ID” DI DESA TELUK AWUR - Kurniawan, Indra; Ulfah, Sofia; Sholikah, Mar’atus; Mubais, Ahmad; Ayu Ramadhani, Nandha; Muhaimin, Muhammad (Journal of Information System and Computer, 2024)
One area that has great tourism potential is Jepara Regency. Jepara is known for its natural beauty, especially its stunning beaches with white sand. Currently, tourists tend to search for information via the internet. The availability of easily accessible information is an important factor influencing the number of visits. However, Teluk Awur Beach is still not optimal in terms of branding and promotion. Research on the Implementation of the Prototype Method in Creating a Tourism Destination Branding Website "Pantaitelukawur.Id" in Teluk Awur Village which aims to digitally brand Teluk Awur beach so that it can be more widely known and make it easier for tourists to find information. The prototype method was used in making this application with stages: (1) Communication, (2) Quick Plan, Modeling and Quick Design, (3) Construction of Prototype, (4) Development, Delivery and Feedback. This method has been proven to make it easier to create a destination branding website for Teluk Awur beach tourism. The prototype method can be used well in developing a destination branding website for Teluk Awur beach tourism. The Teluk Awur beach destination branding information system can display information that tourists are looking for, such as: tourist locations, manager contacts, tourist spots, culinary delights found at tourist attractions..